2020
DOI: 10.1038/s41598-020-71423-x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental regulations, green innovation and intelligent upgrading of manufacturing enterprises: evidence from China

Abstract: relationship model of environmental regulations, green innovation, environmental dynamism and intelligent upgrade is established. Based on the data of Chinese manufacturing listed companies in the process of intelligent upgrade, this article quantitatively analyzes the relationship between environmental regulations, green innovation, environmental dynamism and intelligent upgrading. This article quantitatively studies the role of environmental regulations in promoting intelligent upgrading. It proves the media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 63 publications
0
31
0
Order By: Relevance
“…In addition, since most enterprises in resource-based cities are pollution-intensive [3,47], the intensity of pollutant emission is high. When the intensity of ER increases, a corresponding improvement in production technology and pollution control can be achieved by increasing investment in technological research and development [19,47]. This will have a significant short-term impact on enterprise development and will be detrimental to regional economic development.…”
Section: Effect Of Environmental Regulation On Industrial Transformationmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, since most enterprises in resource-based cities are pollution-intensive [3,47], the intensity of pollutant emission is high. When the intensity of ER increases, a corresponding improvement in production technology and pollution control can be achieved by increasing investment in technological research and development [19,47]. This will have a significant short-term impact on enterprise development and will be detrimental to regional economic development.…”
Section: Effect Of Environmental Regulation On Industrial Transformationmentioning
confidence: 99%
“…For example, implementing strict ERs shifts the negative externalities of enterprise environmental pollution. Consequently, enterprise investment in technological research and development is crowded out, hindering industrial transformation [8,19]. Zhao and Jing [58] reported that the crowding-out impact of TI might cause firms to downsize, diminishing resource use efficiency.…”
Section: Effect Of Technological Innovation On Industrial Transformationmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to avoid the increase of production cost caused by higher environmental regulation, producers tend to make appropriate changes to reduce the compliance cost. Producers should carry out green process improvement and technology research and development to reduce production costs and improve production efficiency (Meng et al, 2020). (2) Promote competition.…”
Section: Literature Review and Theoretical Hypothesismentioning
confidence: 99%